1998
DOI: 10.1152/ajpcell.1998.275.3.c848
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the cloned human intermediate-conductance Ca2+-activated K+ channel

Abstract: The human intermediate-conductance, Ca2+-activated K+ channel (hIK) was identified by searching the expressed sequence tag database. hIK was found to be identical to two recently cloned K+ channels, hSK4 and hIK1. RNA dot blot analysis showed a widespread tissue expression, with the highest levels in salivary gland, placenta, trachea, and lung. With use of fluorescent in situ hybridization and radiation hybrid mapping, hIK mapped to chromosome 19q13.2 in the same region as the disease Diamond-Blackfan anemia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
190
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 230 publications
(216 citation statements)
references
References 33 publications
22
190
0
Order By: Relevance
“…Although others have raised uncertainty about the presence of IK channels in DRG neurons [42,44,77,78], our identification of a clotrimazole-sensitive current suggests that a component of I K(Ca) in these neurons is IK. Other prior observations also support our finding of BK currents in DRG somata [83,102].…”
Section: Discussionmentioning
confidence: 66%
“…Although others have raised uncertainty about the presence of IK channels in DRG neurons [42,44,77,78], our identification of a clotrimazole-sensitive current suggests that a component of I K(Ca) in these neurons is IK. Other prior observations also support our finding of BK currents in DRG somata [83,102].…”
Section: Discussionmentioning
confidence: 66%
“…We have demonstrated that IK and SK channels are activated by benzimidazolinones, including 1-ethyl-2-benzimdazolinone and DCEBIO, as well as the centrally acting muscle relaxants chlorzoxazone and zoxazolamine (5,16). We (17) and others (2,3) have demonstrated that clotrimazole is an inhibitor of IK channels. Recently Chandy and colleagues (18) mapped the molecular binding site for this blocker to the pore of hIK1.…”
mentioning
confidence: 80%
“…While the IK1 and SK channels share roughly 40% homology, their expression patterns and pharmacology are widely disparate, consistent with their unique physiological functions (1). The human IK1 channel (hIK1) is widely expressed, being found in salivary gland, colon, bladder, stomach, lung, smooth muscle, red blood cells, T-cells, and placenta (2,3) where it plays a crucial role in a variety of physiological functions. Indeed hIK1 plays a seminal role in modulating Ca 2ϩ -dependent transepithelial ion transport (4,5), has recently been confirmed to be the Gardos channel of red blood cells (6), and has been proposed to play a role in both vascular remodeling (7) and in modulating vascular tone (8).…”
mentioning
confidence: 97%
“…The predominant KCa channel found in normal human peripheral T cells has a 15-40 pS unitary conductance, is a charybdotoxin (CTX)-sensitive and apamin-insensitive inwardly-rectifying channel that is also known as intermediate conductance (IK) (23,24). A gene encoding IK, called hSK4 (or hIK1, hIKCa1, and hKCa4) has been recently cloned from various human tissues (25)(26)(27)(28). The prominent KCa channel expressed in the human leukemic Jurkat T cell line corresponds to an apamin-sensitive, small-conductance channel (4 -7 pS) (16,17).…”
Section: Camentioning
confidence: 99%